2019
DOI: 10.1088/1748-0221/14/02/p02021
|View full text |Cite
|
Sign up to set email alerts
|

Emanation and bulk fluorescence in liquid argon from tetraphenyl butadiene wavelength shifting coatings

Abstract: A:We study the stability of three types of popularly employed TPB coatings under immersion in liquid argon. TPB emanation from each coating is quantified by fluorescence assay of molecular sieve filter material after a prolonged soak time. Two of the coatings are shown to emanate a detectable concentration of TPB into argon over a 24 hour period, which corresponds to tens of parts per billion in argon by mass. In an independent setup, the dissolved or suspended TPB is shown to produce a wavelength shifting eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…It is used for coating PMTs, detector walls and other elements of optical systems [10,11]. The main disadvantage of any WLS film is low geometrical efficiency, since the light is re-emitted in 4π solid angle, sensitivity to mechanical stress, long term stability [12], scattering and re-absorption of the re-emitted light inside the WLS layer [11,13] and also dependence of the WLS efficiency on the coating method.An elegant idea is to use volume-distributed WLS, which can provide a higher efficiency of re-emission and better collection of the scintillation light. This improves position reconstruction since the re-emission occurs in the point of interaction.It was shown that gaseous xenon doped in LAr works as a volume-distributed WLS shifting the wave length from 128 nm to around 175 nm [14][15][16].…”
mentioning
confidence: 99%
“…It is used for coating PMTs, detector walls and other elements of optical systems [10,11]. The main disadvantage of any WLS film is low geometrical efficiency, since the light is re-emitted in 4π solid angle, sensitivity to mechanical stress, long term stability [12], scattering and re-absorption of the re-emitted light inside the WLS layer [11,13] and also dependence of the WLS efficiency on the coating method.An elegant idea is to use volume-distributed WLS, which can provide a higher efficiency of re-emission and better collection of the scintillation light. This improves position reconstruction since the re-emission occurs in the point of interaction.It was shown that gaseous xenon doped in LAr works as a volume-distributed WLS shifting the wave length from 128 nm to around 175 nm [14][15][16].…”
mentioning
confidence: 99%
“…It is thus necessary to convert the VUV into visible light using a wavelenght shifter (WLS), namely tetraphenyl-butadiene (TPB). An issue with TPB is that it may not be stable over long time scales, in particular due to its dissolving in liquid Ar [12] and peeling off from the substrate under cryogenic conditions [13]. Another known issue is related to difficulties in achieving uniform levels of WLS deposits over large detector areas.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, this may lead to more stable operation of two-phase argon detectors, avoiding the problems of Fig. 3 "Standard" concept of SiPM-matrix readout of two-phase argon detectors with an EL gap WLS degradation and its dissolving in liquid Ar [12], as well as that of WLS peeling off from the substrate.…”
mentioning
confidence: 99%
“…Figure26. Left: proportional EL gain expressed in photoelectrons (PE) recorded by PMT as a function of applied voltage for 10 μm anode wire in liquid Xe[30].…”
mentioning
confidence: 99%